Semantic Systems. In the Era of Knowledge Graphs 16th International Conference on Semantic Systems, SEMANTiCS 2020, Amsterdam, The Netherlands, September 7-10, 2020, Proceedings - Blomqvist, Eva; Groth, Paul; de Boer, Victor; Pellegrini, Tassilo; Alam, Mehwish; Käfer, Tobias; Kieseberg, Peter; Kirrane, Sabrina; Meroño-Peñuela, Albert; Pandit, Harshvardhan J. (Lecture Notes in Computer Science; Information Systems and Applications, incl. Internet/Web, and HCI, 2020)
This open access book constitutes the refereed proceedings of the 16th International Conference on Semantic Systems, SEMANTiCS 2020, held in Amsterdam, The Netherlands, in September 2020. The conference was held virtually due to the COVID-19 pandemic.